2019
DOI: 10.1016/j.bmc.2019.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon versus VHL: Hijacking E3 ligases against each other using PROTACs

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 62 publications
2
79
1
Order By: Relevance
“…Despite the extraordinary importance of VHL in the PROTAC eld, this E3 ligase has not yet been utilized for the successful development of CDK4/6 PROTACs and was even considered to be inappropriate. 37 We followed a combinatorial approach towards VHL-based PROTACs by assembling four different linkers of various lengths and lipophilicities and two VHL ligands bearing different exit vectors for linker connection, 43,61,62 which were ultimately incorporated into the nal palbociclib-derived CDK4/6d. Noteworthy, all PROTACs of the rst, 'amide' subseries (Tables 2 and S6, ESI †) had pronounced ability to suppress CDK4/6 protein levels.…”
Section: Vhl-based Protacsmentioning
confidence: 99%
“…Despite the extraordinary importance of VHL in the PROTAC eld, this E3 ligase has not yet been utilized for the successful development of CDK4/6 PROTACs and was even considered to be inappropriate. 37 We followed a combinatorial approach towards VHL-based PROTACs by assembling four different linkers of various lengths and lipophilicities and two VHL ligands bearing different exit vectors for linker connection, 43,61,62 which were ultimately incorporated into the nal palbociclib-derived CDK4/6d. Noteworthy, all PROTACs of the rst, 'amide' subseries (Tables 2 and S6, ESI †) had pronounced ability to suppress CDK4/6 protein levels.…”
Section: Vhl-based Protacsmentioning
confidence: 99%
“…Another approach developed recently is known as hetero-PROTACs, in which two ligand handles of two PROTACs [VHL and cereblon (CRBN)] were linked together via a linker molecule and tested for the potency of the compound to induce degradation of both ligases. The results showed that VHL could induce degradation of CRBN, but the reverse of this was not observed [ 225 ]. Considering the role of different E3 ligases in inducing the degradation of one another, hetero-PROTACs, can be tried against E3 ligases that are implemented in regulating TGFβ signaling.…”
Section: Emerging Roles Of Protacs and Molecular Gluesmentioning
confidence: 99%
“…Functionalization off of the terminal amine of VH032 has been extensively used in the design of bivalent degraders so we chose this position for linker appendage (Frost et al, 2016;Chan et al, 2018;Girardini et al, 2019). To connect the two ligands, different length alkyl (UNC6851-UNC6853) and PEG linkers (UNC6845-UNC6847) were incorporated to assess the distance required to induce successful EED degradation upon formation of the EED-degrader-VHL ternary complex (Table 1) (Cyrus et al, 2011).…”
Section: Design and Synthesis Of Eed-targeted Bivalent Degradersmentioning
confidence: 99%